THE ROLE OF AGRICULTURAL EXTENSION AGENTS AT THE FOOD SECURITY AND AGRICULTURE OFFICE IN ORGANIC WASTE MANAGEMENT IN MAHAKAM ULU REGENCY - Eka Kasmi Fitrian; Jauchar B; Muh. Jamal; Anwar Alaydrus; Niken Nurmiyati (Journal of Indonesian Rural and Regional Government, 2025)
Organic waste management remains a major challenge for Mahakam Ulu Regency, which faces limited infrastructure, inadequate waste processing facilities, and low levels of environmental literacy among its communities. This study aims to analyze the role of agricultural extension officers within the Department of Food Security and Agriculture in supporting the adoption of household-based organic waste management practices. Using a qualitative descriptive approach through in-depth interviews, field observations, and document analysis, the study identifies four key roles performed by extension officers: facilitator, communicator, motivator, and consultant. These roles are carried out through activities such as Farmer Field School training, socialization of the 3R (Reduce, Reuse, Recycle) concept, assistance in organic fertilizer production, and the provision of technical solutions to local communities. However, the effectiveness of these roles is constrained by the limited number of extension officers, the mismatch in some officers’ educational backgrounds, and the absence of essential waste management facilities such as TPS3R and TPST. The findings highlight that optimizing the role of extension officers requires strengthened institutional support, enhanced technical capacity, and cross-sectoral collaboration to ensure that organic waste management becomes a sustainable practice in Mahakam Ulu.